Trends and determinants of HIV transmission among men who inject drugs in the Pokhara Valley, Nepal: analysis of cross-sectional studies - Sam Hogan; Andrew Page; Felix Ogbo; Sameer Dixit; Rajesh Man Rajbhandari; Bir Rawal; Keshab Deuba (BMC, 2021)
Abstract Background HIV is a major public health issue around the world, especially in developing countries. Although the overall prevalence of HIV in Nepal is relatively low, there are specific sub-populations where the prevalence is far higher than the national average. One of these sub-groups is male people who inject drugs (male PWIDs). In order to understand the reasons for the differences in prevalence, a series of socio-demographic, behavioural and knowledge-based risk factors need to be assessed. Methods The study used a series of 7 cross-sectional survey datasets from Pokhara (Nepal), collected between 2003 and 2017 (N = 2235) to investigate trends in HIV prevalence among male PWIDs by socio-demographic and behavioural and knowledge-based risk factors. A series of logistic regression models were conducted to investigate the association between study factors and HIV. Results HIV prevalence decreased from the levels seen in 2003 (22.0%) and 2005 (21.7%), with the lowest prevalence recorded in 2015 (2.6%), however prevalence has increased in the most recent period (4.9%). A lower risk of HIV was associated with younger age (<=24 years compared to > 24 years, OR = 0.17, 95% CI = 0.10-0.31), being married (OR = 1.91, 95% CI = 1.25-3.02) and shorter duration of drug use (<=4 years compared to > 4 years, OR = 0.16, 95% CI = 0.09-0.29). A higher risk of HIV was associated with low (compared to secondary or higher) education level (OR = 2.76, 95% CI = 1.75-4.36), a lack of addiction treatment (OR = 2.59, 95% CI = 1.64-4.08), and recent use of unsterilized injection equipment (OR = 2.22, 95% CI = 1.20-4.11). Conclusion The prevalence of HIV in male PWIDs in Pokhara has been variable, but overall has reduced in recent years to 2.6% before increasing in 2017 to 4.9%. The main determinants which increase the risk of HIV among male PWIDs in Pokhara are low education level, a lack of treatment for drug addiction and the recent use of unsterilised equipment. Each of these indicate the need to improve addiction treatment and education programs for intra-venous drug use to aid this key population in avoiding risk-taking behaviours.